Kesahan dan kebolehpercayaan Big Five Inventory (BFI) di Malaysia : analisis faktor penerokaan - Nurul Aini Mudayat,; Rafidah Aga Mohd Jaladin,; Norfaezah Md Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aimed to determine the validity and reliability of the Big Five Inventory (BFI) instrument in Malay language translation during the stage of a pilot study. The sample for this study consisted of 150 professional counselors being selected throughout Malaysia with the use of the simple random sampling method. The study is directed via survey design with the adaptation of the questionnaire. The Big Five Inventory (BFI) instrument consists of five subscales namely extraversion, agreeableness, conscientiousness, neuroticism, and openness in a total of 44 items. The data are analyzed through Statistical Package For The Social Science (SPSS). The exploratory factor analysis extracted five factors in personality namely extraversion, agreeableness, conscientiousness, neuroticism, and openness with the retention of 25 items. It proved that the Big Five Inventory (BFI) instrument has assured its validity and reliability for counseling and psychology field in Malaysia. These particular findings demonstrated the importance of validating instruments that are translated into different languages.